Analisis Pembangunan Perdamaian dan Rekonsiliasi Paska Konflik Sunni dan Syiah di Sampang Madura - Ningsih Susilawati; Dahlil Imran (UIN Mataram, 2021)
In a pluralistic society, social conflict often occurs with uncannycomplexity. The Sampang conflict between the Sunni and Shia Muslimcommunities has an impact on several things such as instability, socialuncertainty, also the decadence of unity and integrity. This article wantsto analyze the background of the conflict. In addition, this essay alsoattempts to explain the post-conflict peace building and reconciliationprocess and its important elements. This kind of conflict requires a specialapproach so that similar conflicts do not recur in the future. The methodused in this research is qualitative and descriptive analysis method. Thisresearch found that the conflict happened because of the differenceperception of each groups regarding the history of Islam which affectedstereortye between Sunni as majority group to Shia as Minority group inSampang, Madura. This research also found that the government ofIndonesia both local and Jakarta, failed to facilitate peace building andreconciliation process. It can be shown when the Shia refugees arerejected to come back to their village in Sampang by the Sunni Majority.